The preferences of young adults with Type 1 diabetes at clinics using a discrete choice experiment approach: the D1 Now Study. Issue 12 (19th September 2018) - Mc Morrow, L.; O' Hara, M. C.; Hynes, L.; Cunningham, Á.; Caulfield, A.; Duffy, C.; Keighron, C.; Mullins, M.; Long, M.; Walsh, D.; Byrne, M.; Kennelly, B.; et al.
Abstract: Aim: Attending routine outpatient clinic appointments is a central self‐management behaviour of individuals living with Type 1 diabetes. A large number of young adults with Type 1 diabetes disengage from diabetes services, which may contribute to poor psychosocial and diabetes outcomes. The aim of this study is to elicit preferences from young adults with Type 1 diabetes regarding clinic‐related services to inform service delivery. Methods: A discrete choice experiment was developed to understand the preferences of young adults with Type 1 diabetes for clinic‐related services. Results: Young adults recruited from young adult Type 1 diabetes clinics in 2016 completed the experiment ( n = 105). Young adults with Type 1 diabetes showed a preference for shorter waiting times, seeing a nurse and a consultant, relative to a nurse alone, and a flexible booking system compared with fixed appointment times. Results suggest no preference for a nurse and a doctor, relative to a nurse alone, or other optional services (e.g. seeing dietitians or psychologists), type of HbA1c test and digital blood glucose diaries over paper‐based diaries. Conclusion: This study highlights aspects of routine clinic appointments that are valued by young adults living with Type 1 diabetes, namely shorter waiting times at clinic, the option to see both a nurse and consultant at each visit and a flexible clinic appointment booking system. These findings suggest young adults with Type 1 diabetes value convenience and should help services to restructure their clinics to be more responsive to the needs of young adults. What's new?: This is the first study to use a discrete choice experiment to elicit clinic preferences of young adults (aged 18–25 years) with Type 1 diabetes. This study involved a high level of engagement with our public and patient involvement panel to discuss and refine attributes and levels, and in creating and finalizing the design. The study presents unique insights into the care/treatment preferences of young adults living with Type 1 diabetes for specific characteristics of routine clinic appointments and their willingness to pay for variations in the levels of these characteristics. This study shows that young adults with Type 1 diabetes reported a preference for shorter waiting times at clinics, the option to see both a nurse and consultant at each visit and a flexible clinic appointment booking system.